Potential of the Novel PTA Score to Identify Patients with Peritonsillar Inflammation Profiting from Medical Treatment - Christoph Spiekermann (Disease Markers, 2018)
Peritonsillar inflammation is a common characteristic of both peritonsillar abscess (PTA) and peritonsillitis (PC). The aim of the present study was to apply the PTA score as an objective criterion to identify patients with peritonsillar inflammation (PI) who might profit from medical treatment. Hence, the recently developed PTA score was applied retrospectively on patients suffering from acute tonsillitis, peritonsillitis, and peritonsillar abscess. Analysis of the clinical data, the follow-up, and the initial PTA score was performed. Patients with peritonsillar inflammation show significant higher PTA score values compared to patients with acute tonsillitis without peritonsillar inflammation and healthy controls. Patients with a PTA score ≤ 2 profited from medical treatment consisting of antibiotics in 92.3% of the cases. In 89.2% of the patients with a PTA score > 2, pus was detected during abscess relief. Patients with peritonsillar inflammation who profited from medical treatment had significantly reduced PTA score values and a reduced duration of hospitalization compared to the patients with abscess relief. Thus, the PTA score has the potential as an objective criterion to identify patients with peritonsillar inflammation profiting from medical treatment. Hence, application of the PTA score helps to determine an optimal, individualized treatment approach and might reduce utilization of medical resources.